B. Y. Chen’s Inequalities for Bi-slant Submanifolds in Cosymplectic Space Forms - Gupta, Ram Shankar (Sarajevo Journal of Mathematics, 2024)
In this paper we obtain B. Y. Chen's inequalities for a bi-slant submanifold M of a cosymplectic space form M(c), when the structure vector field ξ of the ambient space is tangent to M. 2000 Mathematics Subject Classification. 53C40, 53B25, 53D15